PENGARUH CARA PEMASAKAN BERBEDA TERHADAP KELARUTAN PROTEIN DAN PERUBAHAN KANDUNGAN KIMIA IKAN SEMBILANG (Paraplotosus albilabris) - Siti Rokayah; Edison Edison; Sumarto Sumarto (Berkala Perikanan Terubuk, 2018)
This study aimed to know the value of rendement, chemical content of fresh sembilang fish meat and after experiencing coocking, and water soluble protein and salt soluble protein.   The method used in this research was experimental method with Completely Randomized Design (CRD) which consists of 4 levels of treatment, with R0 (without coocking), R1 (boiling), R2 (boiling with salt), R3 (steaming). The results showed that the average yield value is 47.7% %, in the proximate analysis of fresh sembilang fish meat contains moisture 59.25%, ash 1.42%, fat 6.01%, and protein content 28.39%. The nutrient content of the fish after the cooking differs based on the analysis performed on each treatment R1, R2, R3 has no significant effect on water content, ash content, and protein content, but has significant effect on fat content.Analysis of water soluble protein had a value 4.16%, 3.97%, 3.85% and 3.18.%